Pengembangan SAK-EMKM Berbasis Aplikasi Android (LAKUM) Terhadap Laporan Keuangan UMKM di Tanjung Pinang - Hendra Candra; Sitti Aliyah Azzahra; Syarif Hidayatullah; Nabilla Akmas (Owner : Riset dan Jurnal Akuntansi, 2025)
MSMEs have an important role in the Indonesian economy, including in Tanjung Pinang – Riau Islands, but limitations in financial management are still obstacles so that the financial statements produced are not in accordance with accounting standards. This research aims to develop an Android-based application called LAKUM (MSME Financial Statements) as a continuation of the implementation of Excel based SAK-EMKM which was previously proven to help MSMEs in simple financial recording. The method used is descriptive qualitative with data collection techniques using observation, interviews with 22 MSME actors and forum group discussions. The analysis technique used thematic analysis and the determination of the sample using purposive random sampling. The results of this study show that the majority of MSME actors in Tanjung Pinang are used to doing simple financial recording even though it is not in accordance with SAK-EMKM with the constraint of not understanding SAK-EMKM and difficulty in making systematic profit/loss reports so that they hope that later the application developed will be easy to use, simple, automatic calculation, advertising-free and flexible. The conclusions of this study theoretically enrich the study of the adoption of TAM based digital accounting technology, as well as show the potential for the integration of SAK-EMKM into mobile applications as a bridge between informal practices and standard reporting. In practical terms, the LAKUM application offers financial recording solutions that are easy, educational, and compliant with standards, so that they can increase efficiency, accountability, and MSMEs' access to financing and business growth.